Effects of Enzymatic Hydrolysis on the Functional Properties, Antioxidant Activity and Protein Structure of Black Soldier Fly (Hermetia illucens) Protein - Batish, Inayat; Brits, Devon; Valencia, Pedro; Miyai, Caio [UNESP]; Rafeeq, Shamil; Xu, Yixiang; Galanopoulos, Magdalini; Sismour, Edward; Ovissipour, Reza (Mdpi, 2020)
Simple Summary According to the FAO, the world's population will reach 9 billion by 2050, and in order to provide enough food, meat production must increase by 100% and food production by 70%. Furthermore, more than 80% of fresh water resources are being used for agriculture, and 40% of the total food produced annually, is wasted. One sustainable agricultural practice involves converting by-products from the food and agriculture industry into valuable biomass, such as black soldier flies. Black soldier fly larvae can feed on by-products, and convert them to protein, carbohydrates, and oil. Black soldier flies could be used for feed and food development using different processing methods including enzymatic hydrolysis. The effects of chemical protein extraction, and enzymatic hydrolysis with Alcalase, papain and pepsin, on the functional properties, antioxidant activity, amino acid composition and protein structure of black soldier fly (H. illucens) larval protein were examined. Alcalase hydrolysates had the highest degree of hydrolysis (p < 0.05), with the highest hydrolysate and oil fraction yield (p < 0.05). Pepsin hydrolysates showed the lowest oil holding capacity (p < 0.05), whereas no significant differences were observed among other enzymes and protein concentrates (p > 0.05). The emulsifying stability and foam capacity were significantly lower in protein hydrolysates than protein concentrate (p < 0.05). The antioxidant activity of protein hydrolysates from protein concentrate and Alcalase was higher than that with papain and pepsin (p < 0.05), owing to the higher hydrophobic amino acid content. Raman spectroscopy indicated structural changes in protein alpha-helices and beta-sheets after enzymatic hydrolysis.
Keywords: insect proteins; black soldier fly; enzymatic hydrolysis; functional properties; antioxidant activity; amino acids composition; Raman spectroscopy; chemometrics